Prospective Associations of Leisure-Time Physical Activity With Psychological Distress and Well-Being: A 12-Year Cohort Study. Issue 1 (4th January 2022) - Werneck, André O.; Stubbs, Brendon; Kandola, Aaron; Oyeyemi, Adewale L.; Schuch, Felipe B.; Hamer, Mark; Vancampfort, Davy; Silva, Danilo R.
ABSTRACT: Objective: This study aimed to investigate the associations of leisure-time physical activity with psychological distress and well-being, and potential mediators. Methods: We used data from the 1970 British Cohort Study ( n = 5197; 2688 men), including waves 34y (2004), 42y (2012), and 46y (2016). Participants reported leisure-time physical activity frequency and intensity (exposure) at age 34 years (baseline); cognition (vocabulary test), body mass index, disability, mobility and pain perception (potential mediators) at age 42 years; and psychological distress (Malaise Inventory) and well-being (Warwick-Edinburgh scale) at age 46 years. Baseline confounders included sex, country, education, employment status, alcohol use, tobacco smoking, and psychological distress. Main analyses included logistic regression and mediation models. Results: Higher leisure-time physical activity intensity at baseline was associated with lower psychological distress at 46y ( β = −0.038 [95% confidence interval CI =−0.069 to −0.007]), but not leisure-time physical activity frequency. Baseline leisure-time physical activity frequency and intensity were associated with higher psychological well-being at 46y (frequency: β = 0.089 [95% CI = 0.002 to 0.176]; intensity: β = 0.262 [95% CI = 0.123 to 0.401]); and total: β = 0.041 [95% CI = 0.013 to 0.069]). Only body mass index at 42y partially mediated the association between leisure-time physical activity frequency (15.7%) and total leisure-time physical activity (6.2%) at 34y, with psychological well-being at 46y. Conclusions: Our findings highlight the role of leisure-time physical activity in psychological distress and well-being, with greater effect sizes associated with higher frequency and intensity of leisure-time physical activity. Future interventions should consider examining potential mediators of the association of leisure-time physical activity with psychological well-being, such as body mass index.